2009
DOI: 10.1055/s-0029-1234082
|View full text |Cite
|
Sign up to set email alerts
|

Whole Body Vibration Does not Enhance Muscle Activation

Abstract: Whether a whole body vibration session can enhance muscle voluntary activation remains debated. This pilot study thus investigated the acute effects of an intervention with whole body vibration versus a "sham" intervention on the voluntary activation of knee extensor muscles. Ten healthy subjects volunteered to participate in two interventions, vibration and sham, in randomized order. Knee extensor muscle voluntary activation, contractile properties and maximal voluntary isometric contraction were assessed bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
25
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 15 publications
10
25
0
5
Order By: Relevance
“…Although they cannot specifically be attributed to any particular group (i.e., time effect), significant improvements in Pts and Ptd were observed after the training period. This result is consistent with previous reports of isometric training of the same muscle group (Rich and Cafarelli, 2000;Maffiuletti and Martin, 2001) and with an acute WBV study (Colson et al, 2009). The potentiation of Pts was associated with an increase in the maximal rates of both twitch development (+dPt/dt) and relaxation (ÀdPt/ dt).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Although they cannot specifically be attributed to any particular group (i.e., time effect), significant improvements in Pts and Ptd were observed after the training period. This result is consistent with previous reports of isometric training of the same muscle group (Rich and Cafarelli, 2000;Maffiuletti and Martin, 2001) and with an acute WBV study (Colson et al, 2009). The potentiation of Pts was associated with an increase in the maximal rates of both twitch development (+dPt/dt) and relaxation (ÀdPt/ dt).…”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with two prior studies which reported that knee extensor muscle activation, determined by a superimposed tetanic train on maximal voluntary contraction, was not changed after 2 and 11 weeks of WBV training (de Ruiter et al, 2003a,b). In addition, recent acute WBV studies have demonstrated that voluntary muscle activation of the knee extensor muscles did not change (Colson et al, 2009) or even decreased (Jordan et al, 2010) after a single WBV session. Even though the reliability of the twitch interpolation technique can be questioned because of the recent reports on animal fibers suggesting that intracellular mechanisms can also account for the increase in torque during the superimposed twitch (Place et al, 2008), we quantified muscle activation by normalizing the superimposed twitch onto the post-contraction potentiated twitch, which was recently recommended as the most valid method at high levels of contraction (Folland and Williams, 2007).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In the current literature, there are some studies reporting no or less effects of WBV intervention (10,11,44). These discrepancies between previous study outcomes in younger and older men arose from the different training procedures used regarding the exercise parameters (side-alternating or synchronous vibration platform device, training period, number of sessions, duration of WBV, and volume of WBV exercises), and the vibration load determined by vibration frequency, vibration amplitude, and joint angle.…”
Section: Introductionmentioning
confidence: 97%